ANALISIS FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN TEXTILE DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mutiara Annisa, 12.05.52.0143; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2016)
The purpose of this study was to examine the effect of financial ratios to predict financial distress on Textile and Garment Firms in the Indonesian Stock Exchange using financial ratios variable which is liquidity, profitability, leverage, sales growth, net profit margin, and firm size as independent variables. While financial distress as measured by the Z-score as the dependent variables. The population in this study were Textile and Garment Firms that listed on Indonesian Stock Exchange. Samples are taken 73 Textile and Garment Firms with purposive sampling method and observation period during five (2009-2013). Relationship and influence between variable is described by using multiple regression analysis. The result showed that liquidity and net profit margin has a significant and positive effect to the financial distress. Profitability, leverage, and sales growth has a negative effect but significant to the financial distress. Whereas firm size had no significant effect to the financial distress. Keywords: Liquidity, Profitability, Leverage, Sales Growth, Net Profit Margin, Firm Size, Financial Distress